2019
DOI: 10.1016/j.jhsg.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bifid Median Nerve and the Cross-Sectional Area as Assessed by Ultrasonography in Healthy Japanese Subjects

Abstract: Purpose: Ultrasonography is useful for evaluating anatomical variations of the median nerve and aids in diagnosing carpal tunnel syndrome by assessing the cross-sectional area (CSA) at the carpal tunnel inlet. The purposes of this study were to investigate the prevalence of the bifid median nerve and to establish reference values for the CSA at the carpal tunnel inlet in healthy participants. Methods: A total of 349 Japanese participants were included (121 men and 228 women, mean age 66.3 years). Study partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Data from 196 hands of 46 men and 52 women (a total of 98) were analyzed. The mean age of subjects was In a study on 349 Japanese participants, there was a significant difference in CSA between women in their sixties and those who were younger (P = 0.02) [29]. In their study, Alsop Loh et al found that aging increases MNCSA [30].…”
Section: Resultsmentioning
confidence: 93%
“…Data from 196 hands of 46 men and 52 women (a total of 98) were analyzed. The mean age of subjects was In a study on 349 Japanese participants, there was a significant difference in CSA between women in their sixties and those who were younger (P = 0.02) [29]. In their study, Alsop Loh et al found that aging increases MNCSA [30].…”
Section: Resultsmentioning
confidence: 93%
“…The second screening was conducted as the full‐text manuscript was sorted. In total, 29 studies were included (Lanz, 1977; Tountas et al, 1987; Amadio, 1988; Iannicelli et al, 2000; Propeck et al, 2000; Gassner et al, 2002; Lindley & Kleinert, 2003; Bayrak et al, 2008; Szopinski & Mazurczak‐Pluta, 2009; Pierre‐Jerome et al, 2010; Granata et al, 2011; Klauser et al, 2011; Mhoon et al, 2012; Walker et al, 2013; Agarwal et al, 2014; Beary et al, 2014; Duymuş et al, 2014; Kasius et al, 2014; Sripathi, Sripathi et al, 2016; Billakota & Hobson‐Webb, 2017; Cartwright et al, 2017; Chen et al, 2017; Kalathummarath, 2017; Petrover et al, 2017; Trachani et al, 2018; Shinagawa et al, 2019; Haris et al, 2021; Park et al, 2021; Dag et al, 2022). These studies were divided into two groups: (a) seven cross‐sectional studies with matching normal or healthy controls, in which the pooled odds ratio and mean difference in CSA were computed (five studies); and (b) 24 cross‐sectional studies without matching control or CTS subjects, in which only the pooled prevalence was computed. The pooled odds ratio of BMN between CTS and normal or control population: 248 BMNs were reported from 2186 CTS wrists, and 100 were reported from 1311 normal (control) wrists.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed an increased prevalence of a bifid median nerve in patients with CTS compared with volunteers; other studies showed a similar prevalence. 14,15 The prevalence of a bifid median nerve in these studies ranges from 10% to 20%. A persistent median artery is a common vascular variant occurring in 10 to 15% of the population.…”
Section: Median Nerve Anatomymentioning
confidence: 91%